ANALYSIS OF THE APPLICATION OF RESTORATIVE JUSTICE IN RESOLVING CRIMINAL CASES IN INDONESIA - Muhammad Junaidi (INJOSEDU: International Journal of Social and Education, 2025)
This research analyzes the application of Restorative Justice (RJ) in resolving criminal cases in Indonesia. RJ is an alternative approach in the criminal justice system that focuses on victim recovery, perpetrator responsibility, and reconciliation between both parties. This research uses a normative-empirical method by examining related regulations and conducting interviews with law enforcement officials, victims and perpetrators. Data sources consist of primary data obtained through interviews and observations, as well as secondary data originating from literature, journals and statutory regulations. The research results show that the application of RJ has provided significant benefits in resolving minor criminal cases and cases involving minors. RJ is proven to be more efficient than conventional justice, because it is able to speed up the resolution of cases, reduce the burden on correctional institutions, and minimize negative impacts for perpetrators and victims. However, the implementation of RJ still faces various challenges, such as differences in understanding among law enforcement officials, community resistance to non-retributive approaches, and the lack of strict monitoring mechanisms in its implementation. Therefore, clearer regulations, training for officers, and increased outreach to the public are needed so that RJ can be implemented optimally and sustainably in the Indonesian criminal justice system.